Advancing Energy-Efficient Technologies in the Internet of Things (IoT): A Comprehensive Analysis - Kaban, Roberto (Karya Techno Solusindo, 2025)
In the era of the Internet of Things (IoT), energy efficiency has become one of the primary research focuses. This study explores five Scopus-indexed papers in the Q1 and Q2 categories, published between 2022 and 2024. The selected papers discuss various strategies to enhance energy efficiency in the IoT context. This review provides a comprehensive overview of the latest efforts in delivering energy-efficient solutions to support the growth and sustainability of IoT. Resource optimization, both in wireless communication infrastructure and data management, is a crucial step in fostering an environmentally friendly IoT ecosystem. Through innovative approaches and intelligent resource optimization, IoT has significant potential to become more energy-efficient and contribute to global environmental sustainability goals. REFERENCES Abdul-Qawy, A. S. H., S. Almurisi, N. M., & Tadisetty, S. (2020). Classification of Energy Saving Techniques for IoT-based Heterogeneous Wireless Nodes. Procedia Computer Science, 171, 2590–2599. https://doi.org/10.1016/j.procs.2020.04.281 Aldin, H. N. S., Ghods, M. R., Nayebipour, F., & Torshiz, M. N. (2024). A comprehensive review of energy harvesting and routing strategies for IoT sensors sustainability and communication technology. Sensors International, 5, 100258. https://doi.org/10.1016/j.sintl.2023.100258 Al-Mutawa, R. F., & Albouraey, F. (2020). A Smart Home System based on Internet of Things. International Journal of Advanced Computer Science and Applications, 11(2). https://doi.org/10.14569/IJACSA.2020.0110234 Alsoufi, M. A., Razak, S., Siraj, M. M., Nafea, I., Ghaleb, F. A., Saeed, F., & Nasser, M. (2021). Anomaly-Based Intrusion Detection Systems in IoT Using Deep Learning: A Systematic Literature Review. Applied Sciences, 11(18), 8383. https://doi.org/10.3390/app11188383 Geetha, S., & Gouthami, S. (2016). Internet of things enabled real time water quality monitoring system. Smart Water, 2(1), 1. https://doi.org/10.1186/s40713-017-0005-y Khan, M. N. U., Cao, W., Tang, Z., Ullah, A., & Pan, W. (2024). Energy-Efficient De-Duplication Mechanism for Healthcare Data Aggregation in IoT. Future Internet, 16(2), 66. https://doi.org/10.3390/fi16020066 Macedo, E. L. C., De Oliveira, E. A. R., Silva, F. H., Mello, R. R., Franca, F. M. G., Delicato, F. C., De Rezende, J. F., & De Moraes, L. F. M. (2019). On the security aspects of Internet of Things: A systematic literature review. Journal of Communications and Networks, 21(5), 444–457. https://doi.org/10.1109/JCN.2019.000048 Milarokostas, C., Tsolkas, D., Passas, N., & Merakos, L. (n.d.). A Comprehensive Study on LPWANs With a Focus on the Potential of LoRa/LoRaWAN Systems. Moutaib, M., Ahajjam, T., Fattah, M., Farhaoui, Y., Aghoutane, B., & El Bekkali, M. (2021). Optimization of the Energy Consumption of Connected Objects. International Journal of Interactive Mobile Technologies (iJIM), 15(24), 176–190. https://doi.org/10.3991/ijim.v15i24.26985 O’Dwyer, E., Pan, I., Charlesworth, R., Butler, S., & Shah, N. (2020). Integration of an energy management tool and digital twin for coordination and control of multi-vector smart energy systems. Sustainable Cities and Society, 62, 102412. https://doi.org/10.1016/j.scs.2020.102412 Ogbebor, J. O., Imoize, A. L., & Atayero, A. A.-A. (2020). Energy Efficient Design Techniques in Next-Generation Wireless Communication Networks: Emerging Trends and Future Directions. Wireless Communications and Mobile Computing, 2020, 1–19. https://doi.org/10.1155/2020/7235362 Politi, B., Foucaran, A., & Camara, N. (2022). Low-Cost Sensors for Indoor PV Energy Harvesting Estimation Based on Machine Learning. Energies, 15(3), 1144. https://doi.org/10.3390/en15031144 Sebestyen, H., Popescu, D. E., & Zmaranda, R. D. (2025). A Literature Review on Security in the Internet of Things: Identifying and Analysing Critical Categories. Computers, 14(2), 61. https://doi.org/10.3390/computers14020061 Tan, F., Pang, S., Cao, Y., Chen, H., & Lv, T. (2024). Energy-Efficient Device-to-Device Communications for Green Internet of Things Using Unmanned Aerial Vehicle-Mounted Intelligent Reflecting Surface. Drones, 8(4), 122. https://doi.org/10.3390/drones8040122 Wu, Y., Lu, P., Bu, X., Liu, S., Zhong, C., & Liu, C. (2022). Computing offloading method with low power consumption constraint for smart grid. Journal of Physics: Conference Series, 2215(1), 012010. https://doi.org/10.1088/1742-6596/2215/1/012010 Xie, J., Chang, Z., Guo, X., & Hamalainen, T. (2023). Energy Efficient Resource Allocation for Wireless Powered UAV Wireless Communication System With Short Packet. IEEE Transactions on Green Communications and Networking, 7(1), 101–113. https://doi.org/10.1109/TGCN.2022.3218314